The Theological and Legal Nature of Oath in Light of the 1983 Code of Canon Law - Nowak, Agnieszka (Prawo Kanoniczne, 2026)
The problem addressed: An oath, in the common understanding, is a form of solemn commitment to perform a specific task or to guarantee the truthfulness of one's words. In the religious sense, an oath is an invocation of God as a witness to the truth and thus constitutes an act of religious worship. The aim of the research conducted: The aim of this article is to present the significance of the institution of oath in the current canon law, with particular emphasis on its religious character and its roots in biblical tradition and Catholic theology. The article also analyses the moral and canonical effects of an oath. The results of the research: The study uses a dogmatic-legal analysis method, which allows for a detailed examination of the content and meaning of the provisions of the Code of Canon Law concerning oath and their practical consequences. This method was supplemented by a historical-legal and canonical approach, which allowed for the development of the institution of oath and its roots in biblical tradition and Church teaching to be revealed. The analysis also covers the conditions for the proper taking of an oath – truthfulness, prudence and justice – and the moral and religious obligations associated with them. The conclusions drawn from the research: The thesis of the study is that an oath in canon law is not merely a formal legal obligation, but an act of a dual nature – theological and legal – in which the religious element determines its moral and canonical effects.